Promoting Inclusive Economic Growth and Development in Angola: A Policy Agenda for Diversification and Innovation - Garwi, Jabulani (HAPSc Policy Briefs Series, 2023)
This policy brief titled "Promoting Inclusive Economic Growth and Development in Angola: A Policy Agenda for Diversification and Innovation" provides a comprehensive analysis of the economic challenges faced by Angola and proposes a policy agenda to foster inclusive growth and development. The brief highlights the heavy reliance on oil exports and the need for diversification, identifies key challenges in sectors such as human capital development and infrastructure, and presents policy recommendations for economic diversification, enhancing human capital, improving infrastructure, and addressing governance and transparency issues. The proposed policy agenda aims to promote sustainable economic development, reduce poverty and inequality, and improve the well-being of the Angolan population. The brief offers valuable insights and practical solutions for policymakers, researchers, and stakeholders interested in addressing the economic challenges and unlocking the potential of Angola’s economy.